FACTORS AFFECTING THE SUCCESS OF MSMEs (Empirical Study on MSMEs in West Kalimantan) - Bambang Wibisono; Abdul Rauf Chaerudin (Jurnal Ekonomi, 2022)
The study aims to know the role of accounting information, business capital, and environmental uncertainty on the success of small and medium enterprises. The population in this study was 13,827 Micro, Small, and Medium Enterprises (MSMEs) in West Kalimantan. The sample of this study was 100 MSMEs, with a sampling method, namely purposive sampling. This type of research is quantitative research by taking data using questionnaires. Data processing techniques use regression analysis. This research shows that using accounting information, capital management, and environmental uncertainty has a positive and significant effect on the success of MSMEs. The implications of this study can increase the use of accounting information and manage the business capital they have correctly; besides that, it is also expected to increase all preparations in facing environmental uncertainty so that business success can be achieved,